2009
DOI: 10.1093/tropej/fmp051
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence Rate of Premature Rupture of Membranes and its Influence on Fetal-neonatal Health: A Report From Mainland China

Abstract: Premature rupture of membranes (PROM) is a common pregnancy complication and is associated with significant risks of fetal and neonatal morbidity and mortality. However, there is a lack of data concerning PROM in China. We investigated the incidence rate and analysed the influence of PROM on fetal and neonatal health. This used data from five specialist hospitals and one general hospital in mainland China. The total number of deliveries and the number of those complicated by PROM were recorded between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 16 publications
2
35
2
Order By: Relevance
“…We hypothesize that there are several reasons why this may be the case (10,19). 1-PROM leads to maternal-fetal infection; this occurs in nearly 1/3 of patients with PROM (20). Intrauterine infection and chorioamnionitis caused by PROM can result in direct injury to the fetal lungs and alveolar type II cells, decreasing the synthesis or release of surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that there are several reasons why this may be the case (10,19). 1-PROM leads to maternal-fetal infection; this occurs in nearly 1/3 of patients with PROM (20). Intrauterine infection and chorioamnionitis caused by PROM can result in direct injury to the fetal lungs and alveolar type II cells, decreasing the synthesis or release of surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…PROM occurring before 37 weeks of gestation is known as preterm premature rupture of membranes (PPROM), while term PROM applies to PROM after 37 weeks of gestation. The incidence of PROM is in the range of 1%–10% worldwide . PROM could lead to several adverse outcomes for both mothers and babies, including respiratory distress syndrome, intraventricular hemorrhage, infection, and even death .…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in 3% of pregnancies and is responsible for approximately one‐third of all preterm births [3]. Despite the many advances in perinatal care, PPROM remains a potentially serious complication with significant risks of maternal and fetal morbidity [3–6]; studies have shown that there is a strong association between PPROM and infection [7].…”
Section: Introductionmentioning
confidence: 99%